2003
DOI: 10.1051/0004-6361:20031185
|View full text |Cite
|
Sign up to set email alerts
|

The faint Cepheids of the Small Magellanic Cloud: An evolutionary selection effect?

Abstract: Abstract. Two problems concerning the faintest Small Magellanic Cloud (SMC) Cepheids are addressed. On the one hand evolutionary tracks fail to cross the Cepheid Instability Strip for the highest magnitudes (i.e. I-mag ∼ 17) where Cepheids are observed; mass-luminosity relations (ML) obtained from evolutionary tracks disagree with mass-luminosity relations derived from observations. We find that the above failures concern models built with standard input physics as well as with non-standard ones. The present w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
9
20
0
Order By: Relevance
“…The effect is larger in the SMC, amounting to ∼ 0.3 dex (vs. ∼ 0.2 dex in the LMC). This result is in agreement with the ones suggested by the evolutionary models of Cordier et al (2003) on the condition of instability strip crossing of low-luminosity Cepheids in the SMC. Also, the discrepancy between the pulsational and evolutionary ML relations (Beaulieu et al 2001) can be largely cured by assuming lower metallicities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The effect is larger in the SMC, amounting to ∼ 0.3 dex (vs. ∼ 0.2 dex in the LMC). This result is in agreement with the ones suggested by the evolutionary models of Cordier et al (2003) on the condition of instability strip crossing of low-luminosity Cepheids in the SMC. Also, the discrepancy between the pulsational and evolutionary ML relations (Beaulieu et al 2001) can be largely cured by assuming lower metallicities.…”
Section: Discussionsupporting
confidence: 92%
“…Currently it has been shown that the observed periods of the first/second overtone double-mode Cepheids in the Magellanic Clouds can be fitted only if we assume that the metallicities of these low-luminosity stars are lower than their fundamental/first overtone counterparts (Kovács 2006). This observation supports the earlier result of Cordier, Goupil & Lebreton (2003), suggesting that Cepheids cannot 'blue-loop' at low-luminosities in the SMC, unless they have systematically lower metallicities than the higher luminosity ones. Stimulated by the above results, the goal of the present study is to use the photometric metallicities in the investigation of the metallicity spread among the Magellanic Cloud Cepheids.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…They found that tracks with metallicity Z = 0.001 correctly reproduce the boundary of the Cepheids towards lower luminosity. According to Cordier et al (2003), Cepheids populating the faint bottom of the instability strip are likely to be metal-poor stars, while variables distributed throughout the instability strip should belong to populations of various metal contents. Romaniello et al (2008) derived direct measurements of the iron abundances of Galactic and Magellanic Cepheids from FEROS and UVES high-resolution and high signal-to noise spectra.…”
Section: Cepheidsmentioning
confidence: 99%
“…Several authors (Dolphin et al 2002(Dolphin et al , 2003Clementini et al 2003;Cordier et al 2003) have suggested that ACs are the natural extension of the Population I Classical Cepheids to lower metal contents and smaller masses. This suggestion is well supported by theoretical investigations (Marconi et al 2004, MFC;Caputo et al 2004, C04) where, based on the constraints provided by pulsation and evolutionary models, it is shown that Anomalous and Classical Cepheids define a common region in the M V -log P plane, with the former ones at lower luminosities and shorter periods, as actually observed in the dwarf irregular galaxy Leo A (Dolphin et al 2002).…”
Section: Introductionmentioning
confidence: 99%